LPPOM MUI North Sumatra Public Relations Communication Strategy in Socializing Halal Certification to Medan City MSME - Amar Fuad Marpaung; Muaz Tanjung (JURNAL AT-TURAS, 2024)
This research aims to explore the communication strategies implemented by Public Relations of LPPOM MUI North Sumatra in socializing halal certification to MSME in Medan City. This study also aims to assess the level of effectiveness of this communication strategy. In the context of processing halal certification, which has significant relevance to products circulating in the Medan City community, a strategic communication approach was taken by LPPOM MUI North Sumatra to MSME traders in this region. This research uses a qualitative approach with the Grounded Research method, which allows researchers to conduct in-depth interviews with key sources. The research sources consisted of the Head of Public Relations of LPPOM MUI North Sumatra and three MSME traders operating on Jl. Tuasan, Medan City. The research results show that North Sumatra LPPOM MUI Public Relations uses various media such as print media, online media and social media in its communication strategy. However, the level of MSME product registration to LPPOM MUI North Sumatra shows a decline every year, with no registration in the 2022-2024 period. These findings indicate that the communication strategy implemented by the Public Relations of LPPOM MUI North Sumatra has not been effective in increasing awareness about halal certification among MSME traders, especially on Jl. Tuasan, Medan Tembung District. The implication is that MSME traders do not understand the process of processing halal certification both online and offline.